Carbon Exchanges: European Experience in Developing the Mechanism of Emission Permit Trading - Svetlana V. Doroshenko; Anna D. Mingaleva (Финансовый журнал, 2020)
The system for trading permits for greenhouse gas emissions is currently being presented as one of the most promising mechanisms for influencing climate problems. However, the regulatory function of this mechanism is not as positively unambiguous as it is represented by international organizations, and its creation, operation and distribution on a global scale are facing many obstacles. The article presents the main results of a study on the process of creating and developing a system for trading in permits for CO2 emissions, implemented in the EU for more than 15 years. In order to identify problems in the functioning of the mechanism for trade in permits for CO2 emissions, a phased analysis of development within the EU has been carried out, and the main institutional obstacles in the existing mechanism have been detected. The analysis of the features of its application is then performed, the strengths and weaknesses of the functioning are determined, and the development prospects are assessed. As a result of the study, it is concluded that, due to the presence of objective contradictions and shortcomings in the existing mechanism for trading permits for CO2 emissions, its validity in its current form does not allow one to achieve the results on reducing emissions and pollution recorded in the UN and EU planning documents on environmental regulation. The main obstacle is the inability to reach, in modern conditions, coordination of the interests of many stakeholders in reducing emissions, which provokes the effect of “carbon leakage”.